ANALISIS INTEGRITAS DIRI PADA SISWA KELAS IX SMP NEGERI 14 P0NTIANAK TAHUN 2020 - Sarima Sarima; H. M. Asrori; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study entitled "Self Integrity in Class IX Students of SMP Negeri 14 Pontianak ”. As for the sub problems, 1) how sincerity in class IX SMP Negeri 14 Pontianak?, 2) how self-consistency of the students SMP Negeri 14 Pontianak?, 3) how persistence of the students in class IX SMP Negeri 14 Pontiannak?, 4) how the students ability to survive SMP Negeri 14 Pontianak?. Destination general research of this to analyze self-integrity in grade IX SMP Negeri 14 Pontianak?. The method used at this research is descriptive method with form of a survey study. Informants in study were 178 people. This study using a sample of 20% so that sample is 42 people of state junior high school 14 Pontianak in 2020. This is study using quantitative approach. The document collection technique the research is technique indirect communication with data collection tools in the questionnaires. Technique data analysis using percentage calculations. A base on the results of data analysis self-integrity in students of SMP Negeri 14 Pontianak in 2020 as a whole reached 79% in the "Medium" category. Keywords: Self Integrity, Students